Flipped Classroom Increases Achievement of Student Learning Outcomes - Komives, Claire (Journal of Engineering Education Transformations, 2018)
The Chemical Engineering Program at San José State University (San José, CA USA) experienced a dramatic increase in students starting in Fall of 2014. From 1999 to 2013, approximately 20- 25 students graduated from the program each year, but since 2014 there have been over 100 beginning the junior year. In addition, the faculty have observed that students’ attention spans, on average, have decreased, in agreement with literature assessments. After giving the Effective Teaching Workshop at Thiagarajar College of Engineering in 2016, the classroom protocol of the Industrial Chemical Calculations Course was modified to include watching the lectures on video prior to the class.Not giving lectures during the class period allowed more time in class to have students practice solving problems. The result has been an increase in student participation in class even with the large number of students, as well as an increase in the achievement of student learning outcomes. This paper will discuss the logistics of the flipped classroom and a presentation of evidence of improved student learning.